INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT) AS A TOOL FOR SUSTAINABLE TOURISM MANAGEMENT: A BIBLIOMETRIC ANALYSIS - Laura Vidal-Serrano; José Miguel Rodríguez-Antón; Luis Rubio-Andrada; Beatriz Narbona-Reina (Cuadernos de Turismo)
The tourism sector has experienced a steady growth in the last decades, becoming one of the key sectors for the development of countries. However, the pandemic caused by COVID-19 brought about an unprecedented social, economic and health crisis that has forced a change in the way tourism is conducted. This article presents a comprehensive bibliometric analysis of different Information and Communication Technologies’ uses in sustainable tourism management to study the literature and serve as a roadmap for future research in this field.